Paliperidone Extended Release Versus Olanzapine in Treatment-Resistant Schizophrenia: A Randomized, Double-Blind, Multicenter Study. Issue 4 (11th July 2022) - Wang, Dandan; Wei, Ning; Hu, Fangzhen; Li, Jianhua; Wang, Yucheng; Qian, Zhiwei; Yang, Miao; Yao, Mingrong; Xia, Yong; Yu, Hong; Tu, Wenzhen; Ye, Minjie; et al.
Abstract: Purpose: Paliperidone is an atypical antipsychotic as effective as other atypical antipsychotics for schizophrenia. However, few studies have explored the efficacy of paliperidone for treatment-resistant schizophrenia. This study aimed to compare the efficacy and safety of paliperidone extended release (ER) versus olanzapine in schizophrenia patients with either poor treatment response or intolerable adverse effects due to standardized antipsychotic therapy. Methods: This 12-week randomized, double-blind, multicenter study compared the treatment efficacy on psychotic symptoms, cognitive functions, and tolerance between paliperidone ER (6–15 mg/d, n = 45) and olanzapine (10–30 mg/d, n = 41) in treatment-resistant or treatment-intolerant patients with schizophrenia. The severity of psychotic symptoms was evaluated by the Positive and Negative Syndrome Scale and the Clinical Global Impression Severity of Illness Scale. The cognitive functions were assessed by the MATRICS Consensus Cognitive Battery. In addition, the metabolic impacts were evaluated by weight gain and waist circumference. Results: Patients with either paliperidone ER or olanzapine treatment showed apparent improvement in psychotic symptoms, without significant intergroup difference. Twelve-week paliperidone ER or olanzapine treatment did not improve the cognitive functions. Both paliperidone ER and olanzapine treatment caused significant increase in weight and waist circumference, and olanzapine had a greater impact on waist circumference than paliperidone ER. In addition, both drugs were well tolerated. Conclusions: Paliperidone ER could be a safe alternative for treatment-resistant schizophrenia.